MANAJEMEN BISNIS SYARIAH KEWIRAUSAHAAN DI PONDOK PESANTREN DAARUL RAHMAN II KABUPATEN BOGOR - Lutfiyah, Konita Oktaviani; Trihantana, Rully; Suryani, Ermi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
The results of the study show that first, sharia management includes planning management, organizing management, directing management, and organizational control management based on the Al-Qur'an and Hadith. Daarul Rahman's business has carried out management in accordance with sharia management. Second, sharia business management in the Daarul Rahman business unit proves that the Daarul Rahman business unit planning implementation uses a profit sharing system between business managers and product owners. The implementation of the organization of the Daarul Rahman business unit consists of business managers and business employees consisting of santri/santriwati or ustad/ustadzah. The implementation of directives for the Daarul Rahman business unit is given direct instructions to members of the collaboration to focus and be more creative in making food or products that will be entrusted. As for the implementation of control over the Daarul Rahman business unit, the manager pays wages to his employees exactly once a month.